Protein Kinases: Evolution of Dynamic Regulatory Proteins - Taylor, Susan S. (2010)
Eukaryotic protein kinases evolved as a family of highly dynamic molecules with strictly organized internal architecture. A single hydrophobic F-helix serves as a central scaffold for assembly of the entire molecule. Two non-consecutive hydrophobic structures termed “Spines” anchor all the elements important for catalysis to the F-helix. They make firm, but flexible, connections within the molecule providing a high level of internal dynamics of the protein kinase. During the course of evolution, protein kinases developed a universal regulatory mechanism associated with a large Activation Segment that can be dynamically folded and unfolded in the course of cell functioning. Protein kinases thus represent a unique, highly dynamic and precisely regulated set of switches that control most biological events in eukaryotic cells.